The Influence of Induced Emotions on Distance and Size Perception and on the Grip Scaling During Grasping - Sun, Chuyang; Chen, Juan; Chen, Yuting; Tang, Rixin (Frontiers in Psychology, 2021)
Previous studies have shown that our perception of stimulus properties can be affected by the emotional nature of the stimulus. It is not clear, however, how emotions affect visually-guided actions towards objects. To address this question, we used toy rats, toy squirrels, and wooden blocks to induce negative, positive and neutral emotions, respectively. Participants were asked to report the perceived distance and the perceived size of a target object resting on top of one of the three emotion-inducing objects; or to grasp the same target object either without visual feedback (open-loop) or with visual feedback (closed-loop) of both the target object and their grasping hand during the execution of grasping. We found that the target object was perceived closer and larger, but was grasped with a smaller grip aperture in the rat condition than in the squirrel and the wooden-block conditions when no visual feedback was available. With visual feedback present, this difference in grip aperture disappeared. These results showed that negative emotion influences both perceived size and grip aperture, but in opposite directions (larger perceived size but smaller grip aperture) and its influence on grip aperture could be corrected by visual feedback.